Fibroblast recruitment as a tool for ovarian cancer detection and targeted therapy. Issue 8 (20th June 2016) - Oren, Roni; Addadi, Yoseph; Narunsky Haziza, Lian; Dafni, Hagit; Rotkopf, Ron; Meir, Gila; Fishman, Ami; Neeman, Michal
Abstract : Metastatic ovarian cancer, the most lethal of gynecologic malignancies, is typically managed by debulking surgery, followed by chemotherapy. However, despite significant efforts, survival rate remains low. We have previously demonstrated, in mouse models, a specific systemic homing of labeled fibroblasts to solid ovarian tumors. Here, we demonstrate the feasibility of utilizing this specific homing of genetically modified fibroblasts for detection and targeted therapy of orthotopic metastatic ovarian carcinoma model in immune‐deficient mice. Using an in vivo metastatic mouse model for ovarian cancer, we demonstrated that fibroblasts expressing fluorescent reporters injected intra‐peritoneally, were specifically recruited to peritoneal tumor nodules (resulting in 93‐100% co‐localization). We further used fibroblasts over expressing the soluble receptor variant of VEGFR1 (s‐Flt1). Mice bearing tumors were injected weekly with either control or s‐Flt1 expressing fibroblasts. Injection of s‐Flt1 expressing fibroblasts resulted in a significant reduction in the ascites volume, reduced vascularization of adherent metastases, and improved overall survival. Using fluorescently labeled fibroblasts for tumor detection with readily available intra‐operative fluorescence imaging tools may be useful for tumor staging and directing biopsies or surgical efforts during exploratory or debulking surgery. Fibroblasts may serve as a beacon pointing to the otherwise invisible metastases in the peritoneal cavity of ovarian cancer patients. Utilizing the recruited fibroblasts also for targeted delivery of anti angiogenic or antitumor molecules may aid in controlling tumor progression. Thus, these results suggest a novel approach for targeting ovarian tumor metastases for both tumor detection and therapy. Abstract : What's new? For patients with metastatic ovarian cancer, survival time is greatly influenced by the extent to which malignant tissue can be removed through debulking surgery. However, even with seemingly complete debulking, very small metastases frequently persist. This study shows that in mice, these otherwise invisible metastases can be identified with fluorescently labeled fibroblasts injected into the peritoneal cavity, where they are recruited specifically to tumor nodules. Mice treated with labeled fibroblasts genetically modified to express the soluble receptor variant of VEGFR1 (s‐Flt1), a negative regulator of angiogenesis, benefited from suppressed ascitic fluid formation and prolonged survival.